Morfologi Telur dan Larva 2 Ascaridia Galli pada Ayam Kampung: Morfology of Ascaridia Galli Egg and Larvae 2 in Domestic Chickens - Wida Wahidah Mubarokah; Joko Daryatmo; Budi Purwo Widiarso; Priyo Sambodo (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2019)
Ascaridia galli (A. galli) is a parasitic nematode that is often found in chickens which causes weight depression and retarded growth, reduced egg production and decreased egg quality. This study aims to determine the morphology of A. galli eggs and larvae 2 (L2) in domestic chickens. Worm eggs are obtained from adult worms that infect domestic chickens naturally. Larvae were obtained from culturing worm eggs in vitro at room temperature for 25 days. A total of 100 worm eggs and 10 L2 were used in this study. Egg measurements included length and width, while larvae included the total length of the larvae carried out with the Axiovision LE software from photographs taken using a light microscope. Data is processed using Microsoft Excel and is presented in the form of mean Â± standard deviation and percent. Results obtained: egg length in this study was shorter than the results of previous studies and the morphology of larvae was the same as previous researchers. Keywords: Ascaidia galli, morphology, eggs, larvae, domestic chickens